Avaliando o avaliador: evidências de um experimento de campo sobre as auditorias da CGU - Zamboni Filho, Yves Basto (2012)
Brazil have nearly achieved universal public service provision on education, health and social assistance, but the quality of these services it is still far behind those of most of developed countries. Auditing institutions are relevant actors on this matter, since is their duty to assess effectiveness and efficiency of public policy delivery. However, the effectiveness of the audit institutions themselves hardly known and debated, especially in Brazil. The works of Olken (2007), Reinikka & Svensson (2004) and Di Tella & Schargrodsky (2000) brought some insights to that discussion, showing how and where best practices policies may work in other countries. In Brazil, evidence based studies about the effectiveness of such policies is scarce. In this thesis, my main goal is to bring some evidence on how effective auditing policies are in Brazil. Using an policy experiment, I assess the effectiveness of CGU's auditing work on the Programa de Fiscalização a partir de Sorteios Públicos. The main issues discussed here are related to program management and public procurement, both connected to federal policies run at local level. Municipalities on the treatment group were subjected to a higher audit probability while the ones on the control group had that probability unchanged. The results suggests that local level managers are responsive to the treatment when it comes to procurement processes, but not when managing other policies. Afterwards I employ an Out of Sample model to establish a human and financial resources allocation mechanism in order to improve efficiency levels of the CGU's field audit work.